Addressing workforce distribution and improving care: insights from trainees - Rebecca McLean; Justin Parr; Brandon M Adams (Australasian Journal of Plastic Surgery)
**Introduction**: Plastic surgeons are maldistributed in New Zealand. Regional centres have fewer surgeons and lower surgeon to population ratios than larger metropolitan areas. There is no published data on the future work intentions of plastic surgical trainees in New Zealand. This study examines the career preferences and intentions of plastic surgery trainees in New Zealand as well as perceived barriers to working in a regional centre.